Implementasi Kurikulum Merdeka dalam Mengembangkan Kemampuan Berpikir Kritis Siswa pada Pelajaran PAI: Study Kasus di SMK Bani Salimah dan SMKN 1 Waringinkurung Kabupaten Serang - Ulfiyah Ulfiyah; Subhan Subhan; Muhamad Shoheh; Wasehudin Wasehudin; Fitri Hilmiyati (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This research is entitled “The Implementation of the Independent Curriculum in Developing Students’ Critical Thinking Skills in Islamic Religious Education (A Case Study at SMK Bani Salimah and SMKN 1 Waringinkurung, Serang Regency)”. This study aims to examine the implementation of the Independent Curriculum in Islamic Religious Education (IRE) and how its application can enhance students’ critical thinking skills. This research employed a qualitative approach with a case study design. Data were collected through interviews, participant observation, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing/verification. The validity of the data was ensured through credibility and confirmability. The findings indicate that the implementation of the Independent Curriculum in both schools has been strongly supported by the institutions, although limitations remain in teacher training and the use of technology. Teachers attempted to overcome these challenges by engaging in self-learning through the “Merdeka Mengajar” platform and independently preparing teaching modules, methods, and learning media. The IRE learning process was oriented towards the development of critical thinking skills using six indicators, although the levels of achievement varied among students. Factors influencing the development of critical thinking include learning motivation, teacher support through differentiated learning, and students’ internal conditions. Meanwhile, obstacles in implementing the Independent Curriculum include limited teacher understanding, low student motivation, insufficient learning facilities, and reluctance of some teachers to adapt to technology. These challenges hinder the optimal development of critical thinking skills, thus requiring improvements in teacher training, strengthening school facilities, and applying more innovative and adaptive learning strategies.